Analisis Feminis atas Agensi Perempuan dan Kekuasaan Patriarki dalam Cerita Rakyat Paser: A Feminist Analysis of Women’s Agency and Patriarchal Power in Paser Folklore - Azahra, Alfyza Nayla; Ulwatunnisa, Marwah (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study examines the representation of women, power relations, and female agency in Paser folklore using a feminist literary perspective. This study focuses on two folktales, namely "Kutukan Dewi Nilam" and “Pego dan Putri Kayangan” which feature female characters in different social and cultural contexts. The method used is a descriptive qualitative method with a literary feminist approach. Data collection was conducted through a literature review and text analysis using an interactive model. The results of the study indicate that the female characters in both stories are depicted as occupying complex positions within the patriarchal structure. In “Kutukan Dewi Nilam,” the female characters are subject to patriarchal power, where their bodies and identities become objects of social control and punishment. On the other hand, in the story “Pego dan Putri Kayangan,” female characters have greater scope to demonstrate their independence through vigilance and decision-making. This finding suggests that folktales not only reflect patriarchal values but also highlight women’s independence in negotiating their positions.